PEMBERIAN PROBIOTIK DALAM PAKAN UNTUK BUDIDAYA IKAN LELE - Dyah Hariani; Tarzan Purnomo (FMIPA : Universitas PGRI Adi Buana, 2017)
The purpose of research is produced using probiotic fermented feed that can increase: the growth rate (SGR), and feed efficiency (FCR). The research was conducted in July and November 2016. The research design used is CRD with 4 treatments and 3 replications, consisting of without given a probiotic (0%), probiotics 5%, 10% and 15% of the total feed given, for all waters treatment probiotics added to one liter every single week. Media for microbial growth added